Comment on "Characteristic Time Scales of Decadal to Centennial Changes in Global Surface Temperatures Over the Past 150 Years" by J. L. Le Mouël, F. Lopes, and V. Courtillot. Issue 4 (23rd April 2021) - Cuypers, Y.; Codron, F.; Crepon, M.
Abstract: Based on Singular Spectral Analysis (SSA) analysis of global earth surface temperature and solar activity (sunspots), Le Mouël et al. (2020, https://doi.org/10.1029/2019EA000671 ) suggest that the variability in Earth surface temperature observed since 1850 is natural and controlled by the Sun. We cannot agree with their conclusions for several reasons: the lack of compelling results from the Fourier spectra and SSA estimates which are provided without confidence intervals, the small radiative forcing associated with the sunspot variability, and finally the simple evidence that the slowly varying components of the temperature and sunspots time show opposite trends in the last 30 years. Key Points: No compelling results showing a significant covariability between sunspot amounts and temperature The radiative forcing associated with slow solar components (60 years, trend) is very weak over the past 150 years The global temperature and slow solar sunspots number components have opposite trend in the last 30 years